Portraying Role of Gender with the Context of Literature - Yelagonda Anjaneyulu, Dr. Babina Bohra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
After a long voyage of making the world better by establishing new laws, developing new objects and modifying ancient concepts and thoughts. Women were still suffering every second and they were still striving for their rights. There is a larger range of women writing now than in previous age. They differ in class, ethnicity, color, age, and cultural and linguistic origins. It is difficult to describe feminism precisely as there are debates among feminists. This article analyses the roles of women and men in society from an interdisciplinary point of view. The author analyses how it creates societal roles throughout varied cultures, and determines women and men’s own sense of identity in literary contexts.